Heat shock and HSP70 regulate 5-FU-mediated caspase-1 activation in myeloid-derived suppressor cells and tumor growth in mice. Issue 1 (7th May 2020) - Pilot, Thomas; Fratti, Aurélie; Thinselin, Chloé; Perrichet, Anaïs; Demontoux, Lucie; Limagne, Emeric; Derangère, Valentin; Ilie, Alis; Ndiaye, Mané; Jacquin, Elise; Garrido, Carmen; Ghiringhelli, François; et al.
Abstract : Background: We have previously shown that 5-fluorouracil (5-FU) selectively kills myeloid-derived suppressor cells (MDSCs) and activates NLRP3 (NOD-leucine rich repeat and pyrin containing protein 3) inflammasome. NLRP3 activation leads to caspase-1 activation and production of IL-1β, which in turn favors secondary tumor growth. We decided to explore the effects of either a heat shock (HS) or the deficiency in heat shock protein (HSP) 70, previously shown to respectively inhibit or increase NLRP3 inflammasome activation in macrophages. Methods: Caspase-1 activation was detected in vitro in MSC-2 cells by western blot and in vivo or ex vivo in tumor and/or splenic MDSCs by flow cytometry. The effects of HS, HSP70 deficiency and anakinra (an IL-1 inhibitor) on tumor growth and mice survival were studied in C57BL/6 WT or Hsp70 −/− tumor-bearing mice. Finally, Th17 polarization was evaluated by qPCR (Il17a, Rorc) and angiogenic markers by qPCR (Pecam1, Eng) and immunohistochemistry (ERG). Results: HS inhibits 5-FU-mediated caspase-1 activation in vitro and in vivo without affecting its cytotoxicity on MDSCs. Moreover, it enhances the antitumor effect of 5-FU treatment and favors mice survival. Interestingly, it is associated to a decreased Th17 and angiogenesis markers in tumors. IL-1β injection is able to bypass HS+5-FU antitumor effects. In contrast, in Hsp70 −/− MDSCs, 5-FU-mediated caspase-1 activation is increased in vivo and in vitro without effect on 5-FU cytotoxicity. In Hsp70 −/− mice, the antitumor effect of 5-FU was impeded, with an increased Th17 and angiogenesis markers in tumors. Finally, the effects of 5-FU on tumor growth can be restored by inhibiting IL-1β, using anakinra. Conclusion: This study provides evidence on the role of HSP70 in tuning 5-FU antitumor effect and suggests that HS can be used to improve 5-FU anticancer effect.